PKM Institutional Strengthening of the Women's Farm Labor Group in Belantih Village, Kintamani District, Bangli Regency - Rustini, Ni Made; Selamet, I Ketut; Purnami, Anak Agung Sri (Jurnal Pengabdian Masyarakat Bestari, 2024)
Women farmers have almost the same role as male farmers, in fact they are directly involved in various stages of activities, especially during the planting and post-harvest period. The development of women farmers in rural areas is fostered through a group forum. To strengthen the institution of the Women Farmers group and focus on coaching, the implementation of the activity was carried out at the Mabi Subak Hall, Belantih Village. It began with a Coordination Meeting of the Farmer Women Group which was opened by the head of Belantih Village who was accompanied by the head of Banjar Mabi hamlet. The Women's Farm Workers Group (KWBT) is an agricultural institution created with the aim of facilitating the activities of women agricultural workers from the orange plant maintenance sector, farm worker equipment assistance, capital to innovation in processing post-harvest orange products into innovative products that have a selling value.